Low-intensity blood flow restriction (LI-BFR) and moderate-intensity improves quadriceps strength and thigh circumference in older women - Jonathan Wibisono Tumali; Rwahita Satyawati; Nur Sulastri (Romanian Journal of Neurology)
Background and objectives. Weakness and atrophy in the quadriceps femoris lead to decreased functional capacity, heightened fall risk, and increased mortality among older women. While moderate-intensity strength training is generally recommended for the elderly, higher-intensity exercises carry a greater risk of injury. Low-intensity exercises with blood flow restriction offer an alternative, providing comparable benefits to high-intensity training. This study aims to evaluate the effects of moderate-intensity and low-intensity blood flow restriction exercises on quadriceps femoris strength and thigh circumference in healthy elderly women. Materials and methods. The sample size was of 88 subjects equally randomized into a moderate-intensity group and a blood-flow restriction group. The moderate-intensity group performed strengthening exercises with a load of ≥40–60% of 1RM, 3 sets, 36 repetitions. The blood-flow restriction group conducted exercises at 20–30% of 1RM, completing 75 repetitions across 4 sets, using a pressure cuff applied to the upper thigh at 50 mmHg or 40% of the Arterial Occlusion Pressure (AOP). Both groups exercised twice a week over a 6-week period. Muscle strength (assessed via dynamometer and 1RM) and thigh circumference were recorded before and after the intervention. Results. After six weeks of intervention, both groups showed a significant increase in muscle strength and thigh circumference (p <0.001). However, no notable differences were observed between the moderate intensity group and the blood flow restriction group regarding quadriceps strength (dynamometer), quadriceps 1RM strength, or thigh circumference (p >0.05). Muscle soreness was reported in 18% of participants in the moderate intensity group. Conclusion. Low-intensity resistance exercises with blood flow restriction in older women can promote strength gains and muscle hypertrophy comparable to moderate-intensity training, while offering a safer alternative.